Influence of the Use of a Collagen Membrane Placed on the Bone Window after Sinus Floor Augmentation-An Experimental Study in Rabbits - Alessandro Perini; Jose Viña-Almunia; Carmen Carda; José Javier Martín de Llano; Daniele Botticelli; Miguel Peñarrocha-Diago (MDPI AG, 2021)
Background: We studied the influence on healing of a resorbable membrane covering the osteotomy site after maxillary sinus grafting, evaluated in different regions of the augmented area. Methods: Maxillary sinus augmentation was performed in 24 New Zealand rabbits. Osteotomy, 4 × 6 mm, were performed bilaterally. A collagenated cortico-cancellous porcine bone was used to fill the elevated region. A collagen membrane was randomly placed over the osteotomy site on one side (MG), and the other side was left uncovered (NMG). The animals were euthanized after 2, 4, and 8 weeks; and histomorphometric analysis was performed in eight different regions. Results: New bone percentages were similar in both groups. There were no statistically significant differences. In MG, the overall percentages were 15.6 ± 7.3%, 22.9 ± 6.1%, and 24.9 ± 12.0% after 2, 4, and 8 weeks, respectively. In NMG, the percentages were 11.2 ± 4.5%, 24.1 ± 5.7%, and 24.5 ± 15.7%, respectively. The proportions of new bone in the various regions after 8 weeks were 31 ± 8.9% and 29.9 ± 9.1% in the bone walls region, 25 ± 10.1% and 32.8 ± 9.1% in the submucosa region, 22.6 ± 21.6% and 10.9 ± 11.5 in the middle region, 17.3 ± 14% and 13.4 ± 9.8% in the close-to-window region, and 21.8 ± 11.6%, 19.1 ± 6.4% in the osteotomy region-for MG and NMG, respectively. Conclusions: In both groups the greatest amounts of bone formation occurred near to the pre-existing bone walls, followed by the sub-mucosa region. The smallest amounts were found in the close-to-window region, followed by the central region. The placement of a collagen membrane to cover the osteotomy site did not influence the amount of new bone formation after sinus grafting.